TRANSFORMATION OF SOCIAL AND HUMANITARIAN SPHERE OF WORLD POLITICS: CHALLENGES FOR RUSSIA - M. M. Lebedeva; L. R. Rustamova (Vestnik MGIMO-Universiteta)
The social and humanitarian issues of world politics are playing an increasingly important role in the political development of the world. The article affirms that humanitarian problems can and should be considered together with the social ones, since in most cases, humanitarian and social processes accompany each other. The article sets the question whether the social and humanitarian spheres are under the process of transformation, and if so, how this process is going. The authors proceed from the assumption that the political organization of the world, which includes the Westphalian system, the system of interstate relations and the political systems of individual states, is transforming and the social and humanitarian spheres are under the influence of this process. The main results of the study are as follows. Firstly, social and humanitarian spheres are intensively developing due to the fact that in the modern world, people and human capital are becoming increasingly significant. Transnationalization within the framework of the Westphalian system leads to the involvement of huge masses of people in international relations. Thus network communications are being intensively formed. In turn, the disintegration of the bipolar system of interstate relations did not lead to the disappearance of the ideological factor, and the social and humanitarian issues became especially important in the interstate interaction. Secondly, in the modern world politics the social and humanitarian issues penetrate ever more intensively into other spheres: military-political and political-economic. In the military- political sphere the social and humanitarian aspects accompany almost all conflicts and they are used in two ways: on the one hand, to counter the enemy (for example in the so called "hybrid wars"), on the other - to reduce tensions and resolve conflicts. In the political and economic sphere, in the 21st century emerges the UN Global Compact, which forms the social responsibility of business on a global scale. In addition, both business and power structures organize various discussion platforms on political and economic issues. The social and humanitarian spheres also get their own development. At present, the sphere of higher education is more than others under the process of transformation. In the future, such social and humanitarian areas of world politics as health care, international tourism, etc also will go through changes. Russia has taken a course to build up its presence in the social and humanitarian spheres of world politics. In this connection on the basis of the analysis the authors give recommendations for Russia.